Outcomes of extended versus standard lymphadenectomy in pancreatoduodenectomy for pancreatic cancer: systematic review and meta-analysis - Yu-Chun Xu; Yin-Hao Shi; Xiao-Feng Li (Frontiers in Oncology)
BackgroundPancreatic cancer has a poor prognosis, and surgical resection is the only curative option. Extended lymphadenectomy (EPD) during pancreatoduodenectomy may improve staging and reduce recurrence, but its survival benefits over standard lymphadenectomy (SPD) remain controversial.MethodsA systematic search of PubMed, Embase, Web of Science, and the Cochrane Library was conducted on March 25, 2025. All studies that met the inclusion criteria were subjected to quality assessment and subsequently analyzed by meta-analytical methods.ResultsNine RCTs involving 1382 patients were analyzed. No significant differences were observed between EPD and SPD in OS (HR = 1.09, p = 0.384), DFS (HR = 1.08, p = 0.506), or recurrence (78.05% vs. 79.64%, p = 0.295). EPD retrieved more positive lymph nodes (MD = 0.66, p = 0.008), but did not improve prognosis. Postoperative morbidity (38.49% vs. 33.27%, p = 0.072), mortality (1.97% vs. 1.33%, p = 0.589), transfusion volume (MD = -31.27, p = 0.469), and hospital stay (MD = -0.15, p = 0.917) were comparable, though EPD increased operative time (MD = 53.24, p < 0.001).ConclusionsEPD reduces lymph node recurrence without improving OS or DFS, suggesting limited prognostic benefit. Its application in pancreatic cancer should be carefully considered.Systematic review registrationhttps://www.crd.york.ac.uk/prospero, identifier CRD42024594566.